Psychometric properties of the Recovery Experience Questionnaire in a coaching population - Braun, L. M.; Wahl, C. A.; Meyer, B. B. (International Journal of Sports Science & Coaching, 2025)
Recognized as the process of psychophysiological unwinding from the demands of work and other stressors, occupational recovery has been a popular topic of study over the past decade. Building on the recovery research in occupational workers and more recently athletes, sport and performance psychology scholars have begun to consider the occupational recovery of the team around the team (i.e., athletic trainers and sport psychology professionals). Like the aforementioned professionals, coaches may be able to use recovery to buffer work-related stressors which can impact their health, work performance, and career longevity. That said, there is a dearth of research on coach recovery, perhaps due to a lack of appropriate measures to study occupational recovery in this specific population. The purpose of the current study, therefore, was to validate the Recovery Experience Questionnaire (REQ) in a coaching population. A sample of 237 collegiate and professional coaches (148 males, 89 females) were recruited from various sports, competitive levels, and roles. In addition to assessing two forms of reliability, a confirmatory factor analysis (CFA) was conducted to evaluate the four latent variable measurement model of the REQ. Furthermore, correlational analyses were used to demonstrate discriminant validity between the REQ and a measure of perceived stress. Collectively, the results suggest that the REQ possesses strong psychometric properties and is a measure worthy of further exploration and use in an elite coaching population.